Crop Yield Prediction Using Epsilon Density Based Prediction - D. Esther Rani, Dr.N.Sathyanarayana, Dr. B. Vishnu Vardhan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Machine learning algorithms play a significant role in data analysis in many disciplines like Agriculture, Food, Medicine, and Twitter Data. Yield prediction is a significant agricultural problem that remains to be solved based on the available data. Earlier yield prediction is an exciting challenge, and this prediction is performed by considering farmers' knowledge of a specific field and crop. Machine learning techniques are used to increase the crop yield, where data is collected from different agricultural sectors. In machine learning, clustering plays a vital role. In this paper, various clustering techniques such as k-Means, Expectation-Maximization, Hierarchical Micro Clustering, Density-Based Clustering, Weight-based clustering are briefed, and a new clustering approach, Epsilon Density-Based Prediction(EDBP), is proposed for obtaining the best crop yield prediction.